Supporting Self-Regulated Learning in Primary Education: Using Written Learning Guides in the Lessons - Liina Kersna; Kristjan-Julius Laak; Liina Lepp; Margus Pedaste (Education Sciences)
Developing children’s self-regulation skills in the school environment is essential for the development of self-directed learners. It is important to note that self-regulation can be developed in the classroom. Teachers play a crucial role in supporting the development of self-regulated learners, including creating the necessary learning environment and designing the tasks used for instruction. The aim of this study is to describe the way teachers chose to structure written learning guides designed for primary school students and to analyse how their use in instruction creates opportunities to support self-regulated learning. We analysed 11 written learning guides, interviewed three primary education teachers who created and used them, and observed 985 min of classroom implementation. The data were analysed using qualitative content analysis combining inductive and deductive methods. The results of this study revealed that the learning guides consist of three parts: an introduction, individual and collaborative tasks with self-assessment, and self-analysis. Our data show that the use of learning guides helped to create a learning environment in the classroom that was supportive of high self-regulated learning. Students were offered a range of options for organising their learning and opportunities to control their learning challenges, including choosing more interesting and difficult tasks, to assess their learning and to collaborate with peers. Teachers supported students through both instrumental instruction and evaluation practises, creating a classroom environment conducive to learning that focused on students’ personal development. We conclude that it is possible to use written learning guides for longer periods of independent or collaborative learning with primary education students. The results provide teachers with practical examples of how to use written learning guides to create conditions for self-regulated learning. For example, combining AI usage with teacher-designed learning guides could increase the benefits and reduce the risks associated with AI-based learning systems.